The way I see it : A personal look at autism & Asperger's - Grandin, Temple (United States of America : Future Horizon, 2008)
Every library, large or small, needs this book on its shelves. Every school, large or small, with the responsibility of educating children with autism or Asperge's needs the guidance this book offers.
Contents Chapter 1. Diagnosis and early intervention Chapter 2: Teaching and education Chapter 3: Sensory issues Chapter 4: Understanding nonverbal autism Chapter 5: Behavior issues
Contiene bibliografía
Keywords: AUTISM; ASPERG´S